The Effect Of Cooperative Learning of Type Think Pair Share Based on Mandailing Culture To Mathematical Problem Solving Ability Of The Students at Middle Secondary School Ali Imron Medan - Miratika, .; Asmin, .; Mulyono, .; Minarni, Ani (Advances in Social Sciences Research Journal, 2018)
The aimed of the research are: (1) to analyze the effect of Cooperative Learning of Type Think Pair Share Based on Mandailing Culture (TPSM) to mathematical problem solving ability (MPSA), (2) to analyze the effect of mathematical initial ability (IMA) to MPSA of the students, (3) to analyze effect of interaction between TPSM and IMA to mathematical problem solving ability of the students. The research population was all students of middle secondary school (MSS) at Sidikalang which consisted of nine classes by taking classes VII-1 and VII-2 as the sampleThe instrument used to measure MPSA of the students is MPSA test. Type of the test is essays test. MPSA data is analyze through Analysis of Variance (ANOVA). Findings of the research are: (1) there is the effect ofTPSMto MPSA of the students, (2) thre is the effect of IMAto to MPSA of the students, (3) there is significant effect of learning approach (TPSM, conventionl approach) and IMA (high, medium, low) to MPSA of the students. Another finding is th time available is not enough to conduct learning trough TPSM, but it can be overcome by good time management. Another one, learning through TPSM make the students become aware to their own culture.